Analysis of the Financial Internal Control Strategies of SME Based on the Background of Big Data - Gao, Jun (Technium Social Sciences Journal, 2022)
With the improvement of the level of market economy and the improvement of the state’s attention to small and medium-sized enterprises (SME), the number of small and medium-sized enterprises in China is gradually increasing, and the market competition is also becoming increasingly fierce. Under the background of big data, the competition faced by small and medium-sized enterprises is more severe. Strengthening the management of financial internal control can ensure that enterprises can successfully complete their development goals and improve their market competitiveness, so as to realize the healthy development of small and medium-sized enterprises. Combined with the significance of financial internal control of small and medium-sized enterprises under the background of big data, this paper emphatically analyzes the problems existing in financial internal control of small and medium-sized enterprises under the background of big data. According to the analysis results, this paper puts forward the strategies of financial internal control of small and medium-sized enterprises under the background of big data, for reference.